2022
DOI: 10.1007/s40121-022-00617-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Favipiravir on Nonsevere, Early-Stage COVID-19 in Japan: A Large Observational Study Using the COVID-19 Registry Japan

Abstract: Introduction Several randomized controlled trials have compared the effectiveness of favipiravir with that of placebo. However, evidence regarding its effect on nonsevere, early-stage coronavirus disease 2019 (COVID-19) remains insufficient. Methods We used the COVID-19 Registry Japan, a nationwide registry of inpatients with COVID-19, for evaluating the effectiveness of favipiravir on patients with nonsevere, early-stage COVID-19. Eligible patients, who did not need su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
3
0
3
Order By: Relevance
“…To our knowledge, currently, a few randomized controlled trials and a large observational study demonstrated the absence of its effectiveness in the examined endpoints consisting of time of viral shedding, hospitalization rate, mechanical ventilator requirement, and mortality rate. [24][25][26] The fact that the Thailand Ministry of Public Health reported that new infections decreased to 1500 cases per day in Bangkok and surrounding areas after the "early testing and early treatment" policy was implemented suggests the potential efficacy of this strategy. Another possible indication of the success of this initiative is that the Siriraj Favipiravir Clinic was able to close within 5 weeks of opening due to the decrease in new cases to a level that could be successfully managed by the normal healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, currently, a few randomized controlled trials and a large observational study demonstrated the absence of its effectiveness in the examined endpoints consisting of time of viral shedding, hospitalization rate, mechanical ventilator requirement, and mortality rate. [24][25][26] The fact that the Thailand Ministry of Public Health reported that new infections decreased to 1500 cases per day in Bangkok and surrounding areas after the "early testing and early treatment" policy was implemented suggests the potential efficacy of this strategy. Another possible indication of the success of this initiative is that the Siriraj Favipiravir Clinic was able to close within 5 weeks of opening due to the decrease in new cases to a level that could be successfully managed by the normal healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Министерство здравоохранения Российской Федерации; 2022. 15 Инструкция по медицинскому применению лекарственного препарата омепразол. https://grls.minzdrav.gov.ru/Grls_View_ v2.aspx?routingGuid=1f929759-b209-4086-8223-ead3658b4df5 16 https://www.whocc.no/atc_ddd_index/?code=A02BC01 койко-дней, для ГИБП и циклофосфамида -3,5 СД/100 пациентов, в 2021 г.…”
Section: результаты и обсуждениеunclassified
“…Среди всех препаратов ВР ЛПП, назначавшихся пациентам с СOVID-19, в том числе для терапии сопутствующих заболеваний, наиболее часто используемым ЛП был омепразол, его потребление в 2022 г. в 1,9 раза превысило 100 DDD/100 койко-дней. Рекомендуемая стандартная доза омепразола в инструкции по медицинскому применению препарата 15 для большинства показаний и DDD, указанная на сайте ВОЗ 16 , составляет 20 мг/сут. Омепразол получали 1112 (89%) пациентов, большинство из них (864 человека) -в дозе 20 мг 2 раза/сут (перорально 862, парентерально 2), 52 (4,7%) пациента -в дозе 40 мг 2 раза/сут (парентерально) и только 196 (17,6%) в дозе 20 мг/сут (перорально).…”
Section: результаты и обсуждениеunclassified
“…A separate study carried out in Japan found over 80% of individuals with mild and moderate cases recovered after 14 days, whereas only 60% of COVID‐19 patients with severe symptoms recovered following treatment with favipiravir [ 150 ]. Thus, favipiravir was concluded to be effective against non‐severe COVID‐19 but has subsequently been deemed non‐essential for treatment of COVID‐19 [ 80 ].…”
Section: Viral Replicationmentioning
confidence: 99%